PENYULUHAN KENAKALAN REMAJA ANAK SEKOLAH DI SEKOLAH MADRASAH TSANAWIYAH NEGERI 1 KABUPATEN GARUT - Iwan Shalahuddin; Indra Maulana (Universitas Malahayati Lampung, 2018)
ABSTRACT Adolescent are a future asset of a nation. In addition to the exciting things with the activities of adolescents in recent times and coaching carried out by student and student organizations, we see also the flow of moral decline which is increasingly striking among some of our youth, who are more famous as juvenile delinquency. In newspapers we often read news about student fights, the spread of narcotics, the use of drugs, liquor, snatches carried out by children in their teens, increasing cases of pregnancy among young women and so on. This is a problem faced by society which is now increasingly widespread. Therefore, the problem of juvenile delinquency should get serious and focused attention to direct teenagers in a more positive direction, which is the emphasis on creating a system to overcome delinquency among teenagers. Keywords: Adolescent, Juvenile Delinquency, Schools